Gap junctions and Wnt signaling in the mammary gland - Fostok, Sabreen F. (2018)
Connexins (Cxs), the building blocks of gap junctions (GJs), exhibit spatiotemporal patterns of expression and regulate the development and differentiation of the mammary gland, acting via channel-dependent and channel-independent mechanisms. Impaired Cx expression and localization are reported in breast cancer, suggesting a tumor suppressive role for Cxs. The signaling events that mediate the role of GJs in the development and tumorigenesis of the mammary gland remain poorly identified. The Wnt pathways, encompassing the canonical or the Wnt/β-catenin pathway and the noncanonical β-catenin-independent pathway, also play important roles in those processes. Indeed, aberrant Wnt signaling is associated with breast cancer. Despite the coincident roles of Cxs and Wnt pathways, the cross-talk in the breast tissue is poorly defined, although this is reported in a number of other tissues. Our previous studies revealed a channel-independent role for Cx43 in inducing differentiation or suppressing tumorigenesis of mammary epithelial cells by acting as a negative regulator of the Wnt/β-catenin pathway. Here, we provide a brief overview of mammary gland development, with emphasis on the role of Cxs in development and tumorigenesis of this tissue. We also discuss the role of Wnt signaling in similar contexts, and review the literature illustrating interplay between Cxs and Wnt pathways.